Pengaruh Penambahan Becker Mewis Duct pada Perfoma Propeller B-series - Husnun Aska Nabilah; Burniadi Moballa; Benedicta Dian Alfanda (Proceedings Conference on Marine Engineering and its Application, 2023)
Pollution due to sea transportation is a problem that requires consistent handling. Recent years of research in the field of shipping have focused on reducing exhaust emissions by increasing fuel efficiency and decarbonization. Decarbonization in the shipping industry can be achieved by using energy saving devices to reduce fuel consumption. The Energy Saving Device commonly used in the shipping world is the Becker-Mewis duct (BMD). This study used a variation of the NACA profile on the Becker-Mewis duct fin. The CFD (Computational Fluid Dynamics) method is used to analyze the thrust coefficient and torque coefficient. Becker-Mewis duct was added to increase thrust and torque values. From the results of the analysis that has been carried out without variations from NACA, the thrust coefficient is 0.1526, the torque coefficient is 0.0162 and the efficiency is 0.5261. With the NACA 4412 variation, it has a thrust coefficient of 0.2579, a torque coefficient of 0.0252 and an efficiency of 0.5728. The NACA 4415 variation has a thrust coefficient of 0.2663, a torque coefficient of 0.0260 and an efficiency of 0.5743. With increased efficiency, the addition of Becker-Mewis duct can increase the performance of the propeller